Pembuatan Brownis Krispy On-The-Go: Inovasi Snack Ringan Program Kreativitas Mahasiswa - Riski Mailisa; Andika Dimas Saputra; Evi Susanti; Titis Wulandari; Tri Wera Agrita (Journal of Community Development, 2024)
Brownies are a type of cake that does not expand, is dense and not as soft as regular sponge cake or black forest cake, but has a distinctive taste, namely a chocolate taste that is very dominant with a strong chocolate aroma. Through our idea of ​​creating brownies in a different packaging form, namely Bronchips, it emerged after conducting a survey of what foods people often carry everywhere. Bronchips, apart from being consumed as a snack, can also be added as a dessert topping or even processed into various desserts on their own. Looking at the product packaging, the target market for this product is young people, urban areas, and those who have a hobby of socializing on social media. This training covers various aspects, from manufacturing techniques, packaging, to marketing strategies. Through this program, it is hoped that students will not only gain culinary skills, but also entrepreneurial skills that can support their economic independence in the future. This activity also supports the development of innovation in the culinary field and encourages a spirit of creativity among students.